2017
DOI: 10.1186/s13287-017-0485-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential long noncoding RNA/mRNA expression profiling and functional network analysis during osteogenic differentiation of human bone marrow mesenchymal stem cells

Abstract: BackgroundMesenchymal stem cells (MSCs) are the most promising cell types for bone regeneration and repair due to their osteogenic potential. MSC differentiation is precisely regulated and orchestrated by the mechanical and molecular signals from the extracellular environment, involving complex pathways regulated at both the transcriptional and post-transcriptional levels. However, the potential role of long noncoding RNA (lncRNA) in the osteogenic differentiation of human MSCs remains largely unclear.MethodsH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 68 publications
2
100
0
1
Order By: Relevance
“…6B) including cytokine-cytokine receptor, NF-kappa B, Toll-like receptor, TNF, Jak-STAT, Fc gamma R-mediated phagocytosis and phagosome. These pathways are involved with stem cell differentiation [3537]. A heat map of the predicted target genes that were highly enriched in the 7 signaling pathways is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6B) including cytokine-cytokine receptor, NF-kappa B, Toll-like receptor, TNF, Jak-STAT, Fc gamma R-mediated phagocytosis and phagosome. These pathways are involved with stem cell differentiation [3537]. A heat map of the predicted target genes that were highly enriched in the 7 signaling pathways is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, many lncRNAs have been considered to regulate osteogenic differentiation [11]. Using human whole transcriptome microarray, Zhang et al profiled the expression and analyzed the functional network of lncRNAs during osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSC), in which a total of 1408 lncRNAs with 623 lncRNAs downregulating and 785 lncRNAs significantly upregulating were detected along with osteogenic differentiation [12]. In this study, we screened osteogenic-related lncRNAs in our established preosteoblast cell line [13] by performing mRNA and lncRNA microarray in combination with KEGG analysis and PCC co-expression analysis [7].…”
Section: Discussionmentioning
confidence: 99%
“…In MC3T3-E1 cells, knockdown of AK045490 significantly increased the expression of osteoblast differentiation marker genes (Alp, Ocn, and Col Iα1), the ALP activity and the formation of mineralized nodules (Figure 2), which were consistent with the phenomenon that the elevated AK045490 expression in bone tissue was accompanied by deteriorated bone microstructure and decreased bone formation in aging mice, as well as in OVX mice. Several canonical signaling pathways, such as the TGF-beta signaling pathway [14][15][16], the MAPK signaling pathway [17], the Hippo signaling pathway [18], the Notch signaling pathway [19], the Jak-STAT signaling pathway, and the Toll-like receptor signaling pathway [12], which are associated with the osteoblast differentiation, have been found to be closely related to lncRNAs. All of these findings indicated that lncRNAs are critical elements in osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Since ncRNAs are central to gene regulation and cellular fates, it can be speculated that most of the EV-mediated regulatory roles elicited in cells/organs are mediated through ncRNAs (18,37). Indeed, ncRNAs are expressed in tissue-specific manner, precisely regulated and actively involved in variety of developmental processes (43)(44)(45)(46)(47)(48)(49)(50), and the lineage specific commitments of stem cells and the maintenance of their characteristic features such as pluripotency, self-renewal, differentiation, and efficiency of cellular reprogramming are largely regulated by ncRNAs (51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Thus, the ncRNAs may govern the equilibrium between pluripotency and differentiation in stem cells, as well as lineage specific fate decisions (61,62).…”
Section: Stem Cell-derived Ncrnamentioning
confidence: 99%